Evaluation and Comparison of the Efficacy of Subcutaneous and Sublingual Immunotherapy for the Treatment of Allergic Asthma in Children - Vojko Berce; Maša Cugmas; Staša Čopi; Brigita Koren; Maja Tomazin; Tina Hojnik (MDPI AG, 2024)
Specific immunotherapy represents the only potentially curative treatment for allergic asthma. Allergens can be administered subcutaneously (SCIT) or sublingually (SLIT). The aim of the current study was to evaluate and compare the efficacy of SCIT and SLIT for the treatment of allergic asthma in children. Our study included 69 children with allergic asthma who underwent immunotherapy for house dust mites or pollen for at least 3 consecutive years. After 3 years of SCIT and SLIT, the median number of asthma exacerbations in the last three months decreased from 2 to 0 (p < 0.01) and from 1 to 0 (p < 0.01), respectively. When comparing the efficacy of SCIT and SLIT, our study revealed a significantly better efficacy of SCIT only in terms of increasing lung function. The median increase in forced expiratory volume in one second (FEV1) after 3 years was 8% with SCIT and −1% with SLIT (p < 0.01). Daily controller therapy could be withdrawn or reduced in 9 out of 16 (56.3%) children who received it before SCIT (p < 0.01) and in 19 of 29 (65.6%) children who received it before SLIT (p < 0.01), but the difference in efficacy was not significant (p = 0.88). Both SCIT and SLIT are effective treatments for allergic asthma in children.